Knowledge, Attitude and Practice toward Breast Cancer among Kurdish Women in Sulaimani Governorate/ Iraq - Amin, Bekhal Abdalwahid; Babakir-Mina, Muhammed; Mohialdeen, Fadhil Ahmed; Gubari, Mohammed I. M. (Kurdistan Journal of Applied Research, 2017)
Breast cancer is a devastating affliction, the frequency of which is gradually increasing all over the world. Cancer may be cured if properly intervened at the right time. The correct treatment, aided by professionals and the right technology can provide critical life support to breast cancer patients. This study was conducted to assessment knowledge, attitude and practice of breast cancer among Kurdish females visited Maternity Teaching Hospital in Sulaimani. A face-to-face interview through a question¬naire to assessment of knowledge and practices toward breast cancer of 500 non-breast cancer women visited Maternity Teaching Hospital was done. Data were computerized and analyzed using Statistical Package for the Social Science (SPSS, version 22). P-value of < 0.05 was considered as statistically significant. Out of 500 participants in the current study on knowledge and practices toward breast cancer among non-breast cancer women, consequently were 227 (45.4%) and 201 (40.2%) practiced breast self-examination(BSE) and clinical breast examination respectively. In this study the participants having no symptoms and lack of knowledge about how to do BSE where regarded as the barriers of not practicing BSE (44.7%, 55.3%) respectively. The most common reason for not doing clinical breast examination (CBE) is fear of the outcome and no sign & symptom of breast cancer (28.8%, 61.9%) respectively. The high education level showed significantly more knowledge of breast self-examination and mammography than Illiterate women P? 0.001 and P? 0.03 respectively. On the other hand, the high education level women showed significantly more practice of breast self-examination P? 0.001. In conclusion, the present study found the facts to the inadequate knowledge of female about breast cancer and recognized the negative influence of low knowledge on the practice of BSE, CBE and mammography and the breast cancer incidence. Therefore, more determinations are needed to develop a positive attitude toward BSE, CBE and mammography screening and practice in Sulaimani.